Resilience and mediation: mechanisms to resolve family conflicts in times of the SARS-CoV-2 pandemic (2022)
The article analyzes the importance of resilience and the usefulness of family mediation as an effective method of family conflict resolution in times of the SARS-CoV-2 pandemic. To meet the objective, an exploratory descriptive analysis was conducted comparing the official figures of complaints of domestic violence published by the National Police of Colombia during the years 2019 and 2020, in the period from January to February and those occurring after March 11, 2020, the date on which the World Health Organization (WHO), classified the epidemic outbreak of SARS-CoV-2 as a pandemic and in coherence with the mandatory preventive isolation in the country. The study was carried out based on the characteristics of the perpetrators, the type of weapons used, and the distinctive elements of the reports before and after the measure. The studies agree that the global health emergency is a completely new condition that will be overcome, based on the contributions of different disciplines that emphasize the importance of the consequences on individual and family mental health, overcoming the intervention focused on prevention and treatment; to move towards an intervention oriented towards conflict resolution. From this perspective, family mediation is configured as a strategy that enhances positive personal and family development. The findings allow us to generate proposals that promote family mediation as an effective method for conflict resolution, prevention, and reduction of violence, with the benefits of resilience.